1983
DOI: 10.1207/s15327752jpa4706_9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intimacy Attitudes: The Intimacy Attitude Scale-Revisited

Abstract: The study evaluated the reliability and validity of a revised version of the Intimacy Attitude Scale originally developed by Amidon. The Cronbach alpha measure of internal consistency showed alpha values between .78 and .86 in five different groups. The test-retest correlation was .57 which improved to .84 after exclusion of three extreme scores. Validity was examined by correlating with several variables. It was concluded that the revised Intimacy Attitude Scale is a reliable instrument with Some degree of Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Nevertheless, there is still little known about the intimacy attitudes of the individuals with more pronounced Machiavellian trait in the interpersonal relationships. To help fill in the aforementioned gap in the psychological literature, this study attempts to investigate the intimacy attitudes of these individuals in their interpersonal relationships by means of the Intimacy Attitude Scale-Revised (IAS-R) (Amidon, Kumar, & Treadwell, 1983). The IAS-R was designed to measure constructs of positive intimacy and negative intimacy within the interpersonal relationships.…”
Section: Machiavellianism and Interpersonal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is still little known about the intimacy attitudes of the individuals with more pronounced Machiavellian trait in the interpersonal relationships. To help fill in the aforementioned gap in the psychological literature, this study attempts to investigate the intimacy attitudes of these individuals in their interpersonal relationships by means of the Intimacy Attitude Scale-Revised (IAS-R) (Amidon, Kumar, & Treadwell, 1983). The IAS-R was designed to measure constructs of positive intimacy and negative intimacy within the interpersonal relationships.…”
Section: Machiavellianism and Interpersonal Relationshipsmentioning
confidence: 99%
“…
The present study investigated the relation between Machiavellianism and intimacy attitudes in the interpersonal relationships. Male (N = 46) and female (N = 56) participants aged 18 to 51 years (M = 31.56, SD = 8.00) were recruited to complete a questionnaire containing Mach IV Scale (Christie & Geis, 1970) and Intimacy Attitude Scale-Revised (Amidon, Kumar, & Treadwell, 1983). The regression analysis has revealed that Machiavellianism is a reliable predictor of the intimacy attitude of an individual, and the hypothesis that Machiavellianism is negatively correlated with positive intimacy and positively correlated with negative intimacy has been confirmed.
…”
mentioning
confidence: 99%
“…The measurement instrument is intimacy attitude scale (IAS) questionnaire by Amidon et al (1983) and the Beck depression inventory (BDI). The pretest and posttest scores of the intimacy attitude scale questionnaire are analyzed in both experimental and control groups.…”
Section: The Proposed Studymentioning
confidence: 99%
“…These days, most governmental agencies attempt to reduce the consequences of depression and there are literally several works to find good solutions to reduce the effects of this issue (Amidon et al, 1983;Fava et al 1996;Bagarozzi, 2001). Bandura (1998), for instance, investigated personal and collective efficacy in human adaptation and change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation